1999
DOI: 10.1021/jp992549u
|View full text |Cite
|
Sign up to set email alerts
|

Guest−Host Interactions in As-Made Al-ZSM-12:  Implications for the Synthesis of Zeolite Catalysts

Abstract: Al-ZSM-12 samples have been prepared with selectively deuterated benzyltrimethylammonium cations as structure-directing agents (SDAs) to study the motion of the SDA and the spatial relationships between the SDA and the zeolite framework. 2 H NMR shows the methyl groups of the structure-directing agent undergo at least two rapid rotations while the benzyl segment is essentially immobile, undergoing only small angle wobbling motions. Cross-polarization and rotational echo double resonance NMR experiments were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 29 publications
6
60
0
Order By: Relevance
“…Variable-temperature solid-state NMR spectroscopy is commonly used to study the dynamics of organic molecules present in the as-synthesized form of zeolites. 21 Generally, molecules occluded within the pores of a zeolite that are not sterically prevented from isotropic reorientation (i.e., the molecule can rotate freely within the pore) and that do not have strong electrostatic interactions with the framework will show a characteristic band sharpening as the temperature increases due to the onset of isotropic reorientation. 13 C CPMAS and 13 C single-pulse MAS NMR variable-temperature experiments performed on sample FER + HMI + TMA in the 298-503 K temperature range are shown in Figure 3a,b.…”
Section: Resultsmentioning
confidence: 99%
“…Variable-temperature solid-state NMR spectroscopy is commonly used to study the dynamics of organic molecules present in the as-synthesized form of zeolites. 21 Generally, molecules occluded within the pores of a zeolite that are not sterically prevented from isotropic reorientation (i.e., the molecule can rotate freely within the pore) and that do not have strong electrostatic interactions with the framework will show a characteristic band sharpening as the temperature increases due to the onset of isotropic reorientation. 13 C CPMAS and 13 C single-pulse MAS NMR variable-temperature experiments performed on sample FER + HMI + TMA in the 298-503 K temperature range are shown in Figure 3a,b.…”
Section: Resultsmentioning
confidence: 99%
“…It may be that Coulombic interactions between the propyl groups and pentavalent anionic silicate centers are the source of the weak host-guest interactions that lead to the formation of the preorganized silicate species driving the evolution of the crystalline zeolite structure. Shantz et al 47 have shown using NMR techniques that benzylic hydrogens of a benzyltrimethylammonium SDA are in close proximity to an Al ion substituted into the framework of ZSM-12, suggesting that the Al distribution may be controlled by the spatial distribution of the SDA within the channels. A similar argument could be made for the SDA directing the siting of Ti or Fe in MFI.…”
Section: Discussionmentioning
confidence: 99%
“…In the final as-synthesized solid products, dipole-dipole interactions between distinct proton-containing moieties associated with organic structure-directing molecules and 29 Si and 27 Al sites in zeolite frameworks allow detailed molecular interactions and geometric relationships to be established [74]. For example, by using cross-polarization (CP/MAS) [70] or Rotational Echo Double Resonance (REDOR) [75,76], charge ordering between the structure-directing species and the zeolite framework can be observed, namely that the negative-charge centers of the zeolite frameworks appear to be directly associated with positive-charge centers of the structure-directing species [19,74,77]. 13 C{ 1 H} and 29 Si{ 1 H} CP/MAS measurements are also being widely used to characterize different isomers of organic structure-directing molecules and their orientations in zeolite cages [78][79][80].…”
Section: Zeolite Crystallization From Alkaline Solutions and Amorphoumentioning
confidence: 99%